A oração eucarística e a sua pluralidade eucológica: uma análise do conceito de participação plena, consciente e ativa - Nascimento, Thales Nogueira Pereira (2024)
The theme of the Eucharistic Prayer was taken up by the Liturgical Reform of the Second Vatican Ecumenical Council. Thanks to the Liturgical Movement initiated before the Council, the Church was able to manifest and reflect the need for a fruitful and concrete liturgical reform. As a result, the council fathers approved the Constitution on the Sacred Liturgy Sacrosanctum Concilium, which laid the foundation for the reform. Then, Pope Paul VI guided the need to reform the Ordo Missae and other Liturgical Books. Of the book reforms, the most important was that of the Roman Missal, in which the great novelty was the elaboration of new formulas for Eucharistic prayer. In liturgical practice prior to the reform, the only expression of Eucharistic prayer present in the Missal was the Roman Canon. This eucology remained the only expression for many centuries, and was still used obligatoryly after the Liturgical Reform of the Council of Trent in the 16th century. Thus, with the Reform of Vatican II, in the desire for a full, conscious and active participation of the faithful, a plurality of eucological texts was presented that express a significant return to the sources of living tradition coming from the East and the West, where theology and liturgy walked together in the celebratory development of Churches and Communities in the first millennium of the Christian era. Although the reform has achieved its objective, even today it is necessary to promote true liturgical formation not only for pastors, but for all the baptized. Therefore, the elaboration of new Eucharistic Prayers, in addition to being an expression of eucological plurality, are also an expression of a desire of the council fathers in the fruitful participation of the Paschal Mystery of Christ celebrated in each Eucharist. In the first chapter of this work, the theological-liturgical aspect will be developed as a starting point for reflection on the Eucharistic Prayer and as an expression of the living tradition of the Church, and its development over the centuries. The second chapter will develop from the theme of the great ecclesiastical event of the 20th century that was the Second Vatican Council and its Liturgical Reform, its antecedents and preparations, highlighting the pastoral concern regarding the participation of the faithful. The reform process and how the new Eucharistic prayers were created. In the third chapter, a pastoral reflection on the Eucharistic Prayers analyzing the post-reformation and the development of liturgical praxis in Brazil from the post-Council to the Third Edition of the Roman Missal of Brazil and the reality of the various acclamations present in it. Therefore, the theme of the Eucharistic Prayer needs to be revisited to understand the celebratory praxis. This is a great heritage of the Church's Tradition that in its plurality of texts cannot be forgotten in the pages of the Missal, but must be increasingly known and celebrated, thus expressing the strengthening and conscious desire to apply proposed concepts for liturgical reform